Does Celebrity Endorsement influence Purchase Intention? Empirical Evidence with Actionable Insights - Nataraj Balasubramanian; Ramesh Kumar J. (Researchers World - International Refereed Social Sciences Journal, 2021)
Purpose: Indians tend to have their decisions influenced by the emotional connect with celebrities; marketers often create advertisements with an emotional appeal to promote attractiveness. With the advent of digital marketing, effectiveness of celebrity endorsements has further gone up. Marketers spend millions of dollars on celebrity endorsements every year. In this scenario, this aims to determine the impact of endorsements in driving the purchase intention of Indians Methodology: This study used the mixed method approach, a qualitative research study followed by a survey approach. Firstly a Focus Group Discussion (FGD) was conducted with the students of Great Lakes Chennai to find the underlying variables. The participants of the discussion shared a common language i.e. English. The FGD group comprised students who like shopping and who have inclination towards celebrity endorsements. In the second part a structured questionnaire was used to collect data from respondents. Findings: The results indicate that the purchase intention of a consumer depends on the reputation, physical attractiveness and popularity of the celebrity endorsing the product. We can also observe that the celebrity fit is not an important factor. Hence the celebrity likability, the controversy risk and the profession of the celebrity are a good driver of purchase intention. Implications: The more a celebrity is admired by a consumer, more is the effect of his/her endorsing a product and hence more can be the purchase intent of the consumers. Hence companies can look at celebrities who are on the favourites list of maximum proportion of the consumers for endorsing a product/service. Originality: Research studies exploring the digital celebrity endorsement is scarce, especially in Indian context. This study has used a mixed method approach to explore the determinants and empirically test it effect.